2016
DOI: 10.1016/j.celrep.2016.05.092
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Consumption of Branched-Chain Amino Acids Improves Metabolic Health

Abstract: Protein restricted, high carbohydrate diets improve metabolic health in rodents, yet the precise dietary components that are responsible for these effects have not been identified. Further, the applicability of these studies to humans is unclear. Here, we demonstrate in a randomized controlled trial that a moderately protein restricted (PR) diet also improves markers of metabolic health in humans. Intriguingly, we find that feeding mice a diet specifically reduced in branched chain amino acids (BCAAs) is suffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
471
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 398 publications
(496 citation statements)
references
References 45 publications
20
471
5
Order By: Relevance
“…Conversely, there was clear reduction in key regulators of the lipid oxidation process, including PGC‐1α, SIRT3, ACAA2, and HADHSC in RedTg livers. It has been previously reported that ad libitum‐fed animals on diets that are high in carbohydrates, but low in proteins, have greater adiposity and the longest lifespan (Solon‐Biet et al., 2014), although the association between the intake of protein/carbohydrates and adiposity is still a matter of debate (Fontana et al., 2016; Maida et al., 2016; Solon‐Biet et al., 2015) including prospective cohort studies of humans (Berryman, Agarwal, Lieberman, Fulgoni & Pasiakos, 2016; Pimpin, Jebb, Johnson, Wardle & Ambrosini, 2016). Nonetheless, the maintenance of body weight in older RedTg mice may be due to higher fat accumulation than in Wt controls, in agreement with our recent study that showed a positive correlation between mouse longevity and conservation of body fat (Mitchell et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, there was clear reduction in key regulators of the lipid oxidation process, including PGC‐1α, SIRT3, ACAA2, and HADHSC in RedTg livers. It has been previously reported that ad libitum‐fed animals on diets that are high in carbohydrates, but low in proteins, have greater adiposity and the longest lifespan (Solon‐Biet et al., 2014), although the association between the intake of protein/carbohydrates and adiposity is still a matter of debate (Fontana et al., 2016; Maida et al., 2016; Solon‐Biet et al., 2015) including prospective cohort studies of humans (Berryman, Agarwal, Lieberman, Fulgoni & Pasiakos, 2016; Pimpin, Jebb, Johnson, Wardle & Ambrosini, 2016). Nonetheless, the maintenance of body weight in older RedTg mice may be due to higher fat accumulation than in Wt controls, in agreement with our recent study that showed a positive correlation between mouse longevity and conservation of body fat (Mitchell et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, dietary protein restriction is an emerging alternative for treating obesity and glucose intolerance induced by a high-fat diet [1,2]. Mediated by FGF21, dietary protein restriction reduces body weight gain, increases energy expenditure, changes food intake and metabolism, and improves glucose homeostasis in obese models [3][4][5][6].…”
Section: Discussionmentioning
confidence: 99%
“…caloric restriction, intermittent fasting) has a positive effect on metabolic health, improving insulin sensitivity and preventing obesity and type 2 diabetes. Dietary protein restriction is an emerging alternative for treating obesity and glucose intolerance induced by a high-fat diet [1,2]. Low-protein diets reduce body weight by decreasing body fat gain, improving glucose tolerance and increasing energy expenditure.…”
Section: Introductionmentioning
confidence: 99%
“…D’Antona et al showed that a BCAA-enriched mixture increased the average life span of mice as well as some markers of mitochondrial health markers in cardiac and skeletal muscle, reporting as well an enhancement in physical endurance (D’Antona et al, 2010). Recently, Fontana et al reported that feeding mice a diet specifically reduced in BCAAs improved glucose tolerance and body composition similar to a standard PR diet (Fontana et al, 2016). …”
Section: What Role Does Dietary Composition Play?mentioning
confidence: 99%